Comprehensible Input FAQs. Issue 39 (2019) - Rogers, Keith
Abstract : Many teachers in the UK are aware of the issues surrounding a grammar-translation approach to teaching the classical languages but do not see any alternatives. One of the purposes of this edition of the Journal of Classics Teaching is to offer a series of articles which provides an overview of an approach called Comprehensible Input. This brief article has been written to provide an introduction to some of the basic questions and point the reader towards the relevant articles.